2001
DOI: 10.1177/019459980112400614
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Effects on Acute and Late Complications after Radiotherapy in Rabbit

Abstract: Soft tissue damages after radiotherapy are an uncommon but serious complication. Late damage after radiation is the principal dose-limiting factor in radiation therapy today and is dependent on vascular pathology as a result of radiation. Pentoxifylline is a methylxanthine derivative that produces dose-related improvement in blood flow, lower blood viscosity, improved erythrocyte flexibility, and increased tissue oxygen levels. An agent that increases blood flow and tissue oxygen content may contribute to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…The prophylactic administration of this antifibrotic in the postirradiation period can reduce late radiation injury by (i) increasing red blood cell deformability and prostacyclin release, (ii) inhibiting the activation of neutrophils and (iii) inhibiting the production of thromboxane (50). In some studies, it has decreased the rate of late radiation reaction, but no proven effect has been observed for acute radiation reactions (50,51).…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…The prophylactic administration of this antifibrotic in the postirradiation period can reduce late radiation injury by (i) increasing red blood cell deformability and prostacyclin release, (ii) inhibiting the activation of neutrophils and (iii) inhibiting the production of thromboxane (50). In some studies, it has decreased the rate of late radiation reaction, but no proven effect has been observed for acute radiation reactions (50,51).…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…As a result, it was concluded that pentoxifylline had a protective effect. [12,13] In a clinical study conducted by the same investigator on 87 cases, pentoxifylline did not have any effects on the early period effects of radiation (p>0.05), whereas there was a significant difference between the late-period results (p<0.05). [14] In a retrospective study examining the late-period effects of RT that are permanent and decrease the quality of life, 30 cases received pentoxifylline 400 mg three times daily for 8 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…[18] Pentoxifylline, which prevents the negative effects of RT by promoting blood circulation and oxygenation in the tissues, fits this definition. [9,13,15] In the present study, we preferred pentoxifylline because it is systemically easy to use, has negligible side effects, and reduces the local effects of RT. We compared, examined, and shared the results of patients with breast cancer that used pentoxifylline for prophylactic purposes following IOERT and WBRT; to the best of our knowledge, this subject has not been studied in the literature yet.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Acute radiodermatitis does not appear to improve with the use of pentoxifylline. 82,83 Pentoxifylline has often been studied in combination with another antioxidant: tocepherol (vitamin E).…”
Section: Pentoxifylline and Tocepherolmentioning
confidence: 99%